2015
DOI: 10.1186/s12967-015-0553-6
|View full text |Cite
|
Sign up to set email alerts
|

Early decline in serum phospho-CSE1L levels in vemurafenib/sunitinib-treated melanoma and sorafenib/lapatinib-treated colorectal tumor xenografts

Abstract: BackgroundAlthough targeted therapies have improved the clinical outcomes of cancer treatment, tumors resistance to targeted drug are often detected too late and cause mortality. CSE1L is secreted from tumor and its phosphorylation is regulated by ERK1/2. ERK1/2 is located downstream of various growth factor receptors and kinases, the targets of most targeted drugs. Serum phospho-CSE1L may be a marker for monitoring the efficacy of targeted therapy.MethodsWe used mice tumor xenograft model to study the assay o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Animal models are extremely critical to assess the efficacy of antitumor agents in the preclinical settings. The subcutaneous colon tumor models are still used to evaluate treatment efficacy against colon tumor growth , including tumor metastasis to the liver . The colon‐26 mouse model, whereby the murine colon‐26 cells are injected subcutaneously into the flank of mice, is commonly used to study the effects of several antitumor agents, including dietary agents .…”
Section: Discussionmentioning
confidence: 99%
“…Animal models are extremely critical to assess the efficacy of antitumor agents in the preclinical settings. The subcutaneous colon tumor models are still used to evaluate treatment efficacy against colon tumor growth , including tumor metastasis to the liver . The colon‐26 mouse model, whereby the murine colon‐26 cells are injected subcutaneously into the flank of mice, is commonly used to study the effects of several antitumor agents, including dietary agents .…”
Section: Discussionmentioning
confidence: 99%
“…Although the melanoma cells we studied harbor Ras mutations that were through v-H-Ras but not N-Ras expression, v-H-Ras induced the phosphorylations of ERK1/2 and MITF (Figures 3-5), and induced the melanogenesis (Figure 1) and metastasis of melanoma cells [24,29]. We have previously reported that Ras activation in melanoma cells induces CSE1L phosphorylation, indicating a link between Ras/Raf/MEK/ERK pathway and CSE1L in cancer progression [24,40]. In our current study, we showed that CSE1L knockdown decreased Ras-induced CREB, MITF, and tyrosinase expressions, in spite of the presence of IBMX ( Figure 5).…”
Section: Discussionmentioning
confidence: 89%
“…However, more comprehensive and in-depth studies are needed in our next plan to explore the precise molecular mechanisms involved in interactions between FLVCR1 and CSE1L. Besides, CSE1L can be detected not only in tumor tissues but also in body fluids, especially in the blood, indicating that CSE1L can be used as a tumor serum biomarker (20)(21)(22). Therefore, our further research plan is to investigate the diagnostic and prognostic value of serum CSE1L in ESCC.…”
Section: Discussionmentioning
confidence: 99%